IMPLEMENTASI KEBIJAKAN KAMPUNG BANTAR DI KECAMATAN PAAL MERAH KOTA JAMBI - Harsens Nursa Prabawa (Jurnal Pemerintahan Dan Keamanan Publik (JP dan KP), 2020)
This Final Report is entitled "The Policy Implementation of the BANTAR (Clean, Safe, and Smart) Village Program in Realizing Environmental Development in the Paal Merah District of Jambi City Jambi Province". The purpose of this observation is to find out how is the policy implementation of BANTAR Village and to find out the outcome of the policy program. The method used in this study is the Qualitative Research method. This research uses data collection techniques through interviews, observation, and documentation. From the results of the discussion showed that the policy implementation of the BANTAR Village program in Paal Merah District has not been running optimally. This is proven by the fact that not all RTs in Paal Merah sub-district participate in the BANTAR Village program. The obstacle experienced is the lack of funds which causes the program has not run optimally then the second obstacles is many agencies involved causes this program to be hampered, so far the team is only an assessment team, not as development team, so there is no sustanibility of this program because the development team has not carried out their duties optimally. To overcome these problems, the authors suggest the need to make a budget for RTs that follow the program, there needs for socialization related to the program, conduct training for accompanying scholars, the need for CSR from companies in the BANTAR village area and reduce the agencies involved in the program. Keywords: Policy, Implementations, Kampung BANTAR